Exploring the Role of Emotions and Moods in Decision Making: Study on the Use of Structured Decision Approach and Intuition - Zulfiqar , Sehar; Islam, A. (International Journal of Engineering and Management Sciences, 2017)
Emotions and moods can play a significant role in the decision making. The present paper contest this point by providing evidence on the two important approaches used in decision making that is structured decision approach and intuition. For this purpose data was gathered from 150 respondents in two different groups. Chi square test, independent sample t-test and logistic regression analysis were used to test the hypothesis. The results of the study reveal that individuals with positive and negative mood state vary significantly in their use of structured decision approach and intuition. The individuals with negative mood state are more likely to use all steps of structured decision approach as compared to the individuals in the positive mood state. The results of the study further reveal that the individual’s emotional state significantly predicted the use of structured approach and intuition in decision making.